2003
DOI: 10.1111/1467-9310.00297
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and impacts of environmental performance in SMEs

Abstract: The paper analyzes empirical evidence from 368 environmentally responsive small and medium‐sized enterprises (SMEs) operating in four industries. The results demonstrate that firms' environmental performance cannot be viewed as a one‐dimensional concept and that determinants of firms' environmental performance depend on the dimension retained. The impacts of firms' environmental performance on their innovativeness and competitiveness vary according to the industry within which they operate. However, impacts on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
108
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 48 publications
19
108
0
3
Order By: Relevance
“…Hillary (2004) 8 EU countries SME 1-249 survey (unclear, approx. 120 SMEs) Peters & Turner (2004) UK no clear SME definition interview (62 SMEs) Pimenova & van der Vorst (2004) UK micro 1-9, SME 10-249 survey (13 micro, 9 SMEs) Rothenberg & Becker (2004) USA small <= 20, medium > 20 survey (54 small, 74 medium) interview (7 SMEs, 9 advisers) Simpson et al (2004), Taylor et al (2003) UK SME < 250 survey (63 SMEs) interview, site visit (15 SMEs) Ammenberg & Hjelm (2003) Sweden SME 0-249 interviews (25 SMEs) Kannan & Boie (2003) Germany SME < 500 case study (1 SME) Lefebvre et al (2003) Canada SME < 500 survey (368 SMEs) Naffziger et al (2003) USA SME <= 500 survey (100 SMEs) Revell (2003) Japan small < 50 interview (20 small) Vernon et al (2003) UK micro < 10 focus group (25 micro, 34 staff) Friedman & Miles (2002) UK SME < 250 interview (61 SMEs, 21 stakeholders) Gunningham & Sinclair (2002) Australia small < 50 interview (13 small, 8 stakeholders) Hansen et al (2002) 5 EU countries SMEs <= 250 interview (20 SMEs) Schaper (2002) Australia small < 20 survey (154 small) Rutherfoord et al (2000) UK, Netherlands small < 50 interview (40 small) Tilley (2000), Tilley (1999) UK small < 50 interview (60 small) Non-empirical journal articles Clement & Hansen (2003) Content analysis of documents on Nordic SME environmental funding schemes Hoevenagel & Wolters (2000) Secondary data on Dutch SME (< 100 staff) use of environmental intermediaries Shearlock et al (2000) Studied a database of environmental service firms, but not SMEs using the services Walley & Taylor (2002) Literature review which identified and defined a typology of green entrepreneurs…”
Section: Methodsmentioning
confidence: 99%
“…Hillary (2004) 8 EU countries SME 1-249 survey (unclear, approx. 120 SMEs) Peters & Turner (2004) UK no clear SME definition interview (62 SMEs) Pimenova & van der Vorst (2004) UK micro 1-9, SME 10-249 survey (13 micro, 9 SMEs) Rothenberg & Becker (2004) USA small <= 20, medium > 20 survey (54 small, 74 medium) interview (7 SMEs, 9 advisers) Simpson et al (2004), Taylor et al (2003) UK SME < 250 survey (63 SMEs) interview, site visit (15 SMEs) Ammenberg & Hjelm (2003) Sweden SME 0-249 interviews (25 SMEs) Kannan & Boie (2003) Germany SME < 500 case study (1 SME) Lefebvre et al (2003) Canada SME < 500 survey (368 SMEs) Naffziger et al (2003) USA SME <= 500 survey (100 SMEs) Revell (2003) Japan small < 50 interview (20 small) Vernon et al (2003) UK micro < 10 focus group (25 micro, 34 staff) Friedman & Miles (2002) UK SME < 250 interview (61 SMEs, 21 stakeholders) Gunningham & Sinclair (2002) Australia small < 50 interview (13 small, 8 stakeholders) Hansen et al (2002) 5 EU countries SMEs <= 250 interview (20 SMEs) Schaper (2002) Australia small < 20 survey (154 small) Rutherfoord et al (2000) UK, Netherlands small < 50 interview (40 small) Tilley (2000), Tilley (1999) UK small < 50 interview (60 small) Non-empirical journal articles Clement & Hansen (2003) Content analysis of documents on Nordic SME environmental funding schemes Hoevenagel & Wolters (2000) Secondary data on Dutch SME (< 100 staff) use of environmental intermediaries Shearlock et al (2000) Studied a database of environmental service firms, but not SMEs using the services Walley & Taylor (2002) Literature review which identified and defined a typology of green entrepreneurs…”
Section: Methodsmentioning
confidence: 99%
“…It would also be useful to test the model in other tourist sectors, such as catering and transportation. In addition, because this study was conducted among more high-rated and larger hotel units, further research could concentrate on low-rated and smaller firms, which are usually more flexible and less formalized in their green marketing practices (Lefebvre, Lefebvre, & Talbot, 2003).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Furthermore, in a study on the determinants of SMEs' environmental performance, Lefebvre et al (2003) assume that larger SMEs would be more likely to have a higher environmental performance because they can benefit from scale economies in their effort to go green. This potential explanation is also mentioned in other studies from the CSR literature (Elsayed & Paton, 2007;Orlitzky, 2001).…”
Section: Size Of the Institutionmentioning
confidence: 99%